2006
DOI: 10.1207/s15324796abm3102_8
|View full text |Cite
|
Sign up to set email alerts
|

Pain and wound healing in surgical patients

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(92 citation statements)
references
References 39 publications
2
89
0
1
Order By: Relevance
“…The findings of the observational studies, which provide evidence of an association between stress and healing, are supported by one of the intervention studies [47].T w o studies [42,49] reported nonsignificant findings and one [60] found that a diagnosis of posttraumatic stress disorder (PTSD) augmented healing. Another [45] did not find a statistically significant relationship between depression and levels of MMPs in wound fluid; however, they did find a negative relationship with physiological measures of stress.…”
Section: Main Finding From the Systematic Reviewmentioning
confidence: 88%
See 3 more Smart Citations
“…The findings of the observational studies, which provide evidence of an association between stress and healing, are supported by one of the intervention studies [47].T w o studies [42,49] reported nonsignificant findings and one [60] found that a diagnosis of posttraumatic stress disorder (PTSD) augmented healing. Another [45] did not find a statistically significant relationship between depression and levels of MMPs in wound fluid; however, they did find a negative relationship with physiological measures of stress.…”
Section: Main Finding From the Systematic Reviewmentioning
confidence: 88%
“…In contrast, comparison between the experimental punch biopsy wound studies [49,50,63,64,67,68] was facilitated by the fact that the wounds in these studies were of a standard size with reduced measurement variability. Indeed, most punch biopsy studies demonstrated the reliability and validity of their measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific surgical techniques might influence recovery time in the acute postoperative period [37][38][39]. The length of pain exposure in the acute postoperative period is associated with the development of chronic postsurgical pain [40,41]. Optimal pain reduction in the acute postoperative period seems to be important, not only for fast recovery and rehabilitation in the short-term, but for the prevention of CPSP as well [42,43].…”
Section: Discussionmentioning
confidence: 99%